The effects of atomic oxygen and ion irradiation degradation on multi-polymers: A combined ground-based exposure and ReaxFF-MD simulation. (November 2022) - Zhang, Yifan; Yuan, Heng; Yan, Weiqing; Zhang, Zhiqiang; Chen, Shunian; Liao, Bin; Ouyang, Xiao; Chen, Lin; Zhang, Xu
Highlights: The intensive investigation and comparison of the degradation behavior and structural transformation of Mylar, Teonex, Vectra, Kapton and Teflon under AO exposure and Fe + -Ion irradiation in a space environment. ReaxFF-MD simulations verify the essential interatomic interactions between AO/Fe + and the selected polymers and draw additional information. Abstract: Polymers are ubiquitous in the aerospace industry, and their atomic oxygen (AO) exposure and ion irradiation stability are a chief concern. In this work, the AO and ion-irradiation degradation mechanisms for Mylar, Teonex, Vectra, Kapton and Teflon were investigated by adopting ground-based simulated environments (AO exposure and Fe + irradiation tests) and reactive molecular dynamics (ReaxFF-MD) simulations. Mylar, Teonex, Vectra and Kapton show analogous AO degradation mechanisms, which are associated with the fracture and oxidation of the molecular chain skeleton and the emission of volatile small molecular species, resulting in mass loss. Teflon exhibits distinctive AO erosion kinetics, and the existence of an overall drift of the macromolecular chain with AO emission greatly compromises its stability. Moreover, Mylar, Teonex, Vectra and Kapton also exhibit comparable irradiation damage mechanisms and radical evolution. The elimination of C=O, CO-C and CN (only for Kapton) bonds and the generation of phenyl, phenoxyl and ketone radicals are the primary consequences of Fe + irradiation. However, only subtle C-F bond breakage for Teflon can be detected during Fe + irradiation, and the corresponding peroxide radicals are formed after contact with air atmosphere. Graphical abstract: Image, graphical abstract